Photocatalytic treatment of 4-chlorophenol in aqueous ZnO suspensions : intermediates, influence of dosage and inorganic anions. - Gaya, Umar Ibrahim; Abdullah, Abdul Halim; Zainal, Zulkarnain; Hussein, Mohd. Zobir (Elsevier, 2009)
The photocatalytically driven removal of eco-persistent 4-chlorophenol from water using ZnO is reported here. Kinetic dependence of transformation rate on operating variables such as initial 4-chlorophenol concentration and photocatalyst doses was investigated. A complete degradation of 4-chlorophenol at 50 mg L−1 levels was realised in 3 h. Analytical profiles on 4-chlorophenol transformation were consistent with the best-line fit of the pseudo zero-order kinetics. The addition of small amounts of inorganic anions as SO42−, HPO4−, S2O82− and Cl− revealed two anion types: active site blockers and rate enhancers. Fortunately, Cl− and SO42− commonly encountered in contaminated waters enhanced the rate of 4-chlorophenol degradation. The reaction intermediates and route to 4-chlorophenol mineralisation were elucidated by combined RP-HPLC and GC–MS methods. In addition to previously reported pathway products of 4-chlorophenol photo-oxidation catechol was detected. A radical mechanism involving o-hydroxylation is proposed to account for the formation of catechol.